Efficacy of Voriconazole Versus Itraconazole in the Treatment of Dermatophyte Infections - Jamal, Jweena Bintey; Akhter, Khandaker Rokshana; Kabir, Ahsanul (Bangladesh Armed Forces Medical Journal, 2026)
Background: Dermatophyte infections, commonly referred to as tinea or ringworm, are superficial fungal diseases that involve keratinized tissues such as the skin, hair, and nails. Their pathogenesis is linked to fungal adhesion, tissue penetration, and host inflammatory responses. Several antifungal agents are used in treatment, including terbinafine, griseofulvin, fluconazole, and itraconazole. Voriconazole, a second-generation triazole with broad-spectrum activity, inhibits fungal cytochrome P450–dependent 14-α-lanosterol demethylation, disrupting cell membrane integrity. Itraconazole, another triazole, also interferes with ergosterol synthesis via cytochrome P450 inhibition and has been widely applied in dermatophytosis management. Objectives: To compare the therapeutic efficacy of voriconazole and itraconazole in patients with dermatophyte infections. Methods: This quasi-experimental study was conducted in Department of Dermatology & Venerelogy, Combined Military Hospital (CMH), Sylhet. Total 100 patients aged between 15 to 70 years, with recurrent and chronic dermatophyte infections all over the body, except those who have not responded to conventional antifungals taken for almost 4 weeks were enrolled for study. Then subjects were allocated in to two group- Group-A (patients treated by oral voriconazole 200mg twice daily) and Group-B (patients treated with oral itraconazole 100mg twice daily). Then treatment outcome was compared. All information was recorded in data collection sheet. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Result: The mean age of participants was 34.1 ± 6.2 years in Group A and 32.9 ± 6.1 years in Group B. Males comprised 80% of Group A and 60% of Group B, with no significant differences in age or sex distribution between groups (p > 0.05). Complete clinical cure was observed in 72% of patients treated with voriconazole compared to 44% in the itraconazole group. This difference was statistically significant (p = 0.001). Conclusions: Voriconazole demonstrated superior efficacy compared to itraconazole in the management of dermatophyte infections. It appears to be a safe and effective oral antifungal option for patients with chronic or resistant disease. Bangladesh Armed Forces Med J Vol 58 No (2) December 2025, pp 57-65